Mejoramiento genético. Mejoramiento de caracteres. Virología - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1986)
The main emphasis of the BCMV research at CIAT-Palmira was the characterization of black root resistance mechanisms and identification of new resistance sources. Concerning BYMV, the main research effort in 1985 was the characterization of the new BYMV-0I (Orfeo-INIA) strain, which occurs in Chile. This new strain has been isolated to look for new sources of resistance and to learn more about the epidemiology of BYMV in Chile, particularly its origin. In relation to BGMV, a major revision of research strategies was initiated as the coordination of the BGMV project was centralized at CIAT headquarters. A pedigree analysis was carried out of all the golden mosaic-improved lines and other bred materials that have shown good agronomic performance under BGMV pressure. Substantial progress was made in the efforts to utilize sources of resistance to BGMV by using resistant lines such as A 429, DOR 302, and DOR 303. (CIAT)